Psychometric Properties of the Filipino Version of Harris-Hip Score Among Patients with Osteoarthritis and Hip Fractures: A Cross-Cultural Validation Study - Tan, Diovince; Angeles, Byron; Braganza, Carmelo; Fernandez, Carlo (Philippine Journal of Orthopaedics, 2025)
Background: The Harris Hip Score (HHS) is a widely used instrument for assessing hip function and quality of life in patients with hip conditions. However, the questionnaire has not been validated in Filipino, limiting its use in the Philippines. This study aimed to translate, culturally adapt, and validate the HHS for Filipino-speaking patients with osteoarthritis or hip fractures to enhance its clinical and research applicability. Methodology: This cross-sectional, cross-cultural validation study followed established protocols, including forward and backward translation, expert panel review, pretesting, and field testing. A total of 120 bilingual Filipino patients (20 for pretesting and 100 for field testing) with osteoarthritis or hip fractures participated. Psychometric evaluations assessed content validity (S-CVI/Average ≥0.90), internal consistency (Cronbach’s alpha), test-retest reliability (Intraclass Correlation Coefficient, ICC), and construct validity through correlations with the WOMAC and SF-36 scores. Results: The Filipino version of the HHS demonstrated strong psychometric properties. Internal consistency was acceptable (Cronbach’s alpha = 0.724), while test-retest reliability was excellent (ICC = 0.921, p < 0.001). Content validity was robust, with an S-CVI of 0.963. Construct validity was confirmed through significant correlations with WOMAC and SF-36 domains, supporting both convergent and discriminant validity. Pretesting revealed that the translated questionnaire was culturally relevant, easily understood, and applicable to the target population. Field testing further validated its reliability and clinical usability. Conclusion: The Filipino version of the Harris Hip Score is a valid and reliable instrument for evaluating hip function and quality of life in Filipino-speaking patients with osteoarthritis or hip fractures. It offers clinicians and researchers a more culturally accessible tool for Filipino-speaking patients to assess treatment outcomes. Future studies should explore its responsiveness over time and evaluate its applicability to a broader range of populations.